Altered serum fatty acid composition in geriatric depression - Marx, Ivo; Herpertz, Sabine (Journal of neural transmission, 2017)
Fatty acids (FA), mainly polyunsaturated (PUFA) of n-3 or n-6 types, may influence neuropsychobiological processes. Decreased levels of n-3 PUFA have been shown to be related to major depression and supplementation of n-3 PUFA seems to contribute to improved depression treatment outcome. The profiles of serum FA profiles in patients with geriatric depression have not been thoroughly studied yet. The present study investigated the FA profiles of patients with geriatric depression and of mentally healthy elderly individuals. Serum FA profiles of 36 inpatients with geriatric depression who fulfilled DSM-IV criteria for unipolar major depression were compared with those of 37 control subjects. Patients with geriatric depression, irrespective of gender, exhibited lower total FAs, as well as significantly lower concentrations of total n-3 PUFA and eicosapentaenoic acid, though the groups did not differ with regard to Body Mass Index. The findings of the present study point to an association between lower FA serum levels and geriatric depression. Further investigations with larger samples and dietetic interventions may provide deeper insights into the role of eicosapentaenoic acid and total n-3 PUFA in the development and treatment of geriatric depression.
First online: 29 September 2015
Gesehen am 17.05.2018